The Role of Class Teachers in Dealing with Students with Special Needs in Regular Schools - Mahdalena Leksana, Dinar; Sa’adah, Sa’adah; Putri Firnanda, Wahyu; Nadhiroh, Shoviyatun; Khusnah, Asmaul (ACIECE, 2019)
his purpouse aims to explain the role of teachers in dealing with students with special needs in regular schools. This study uses qualitative methods data collected through observation,interviews, and documentation. Research subjects are teachers in regular schools. The object of this study is the teacher's role in the form of attitudes towards children with special needs. The research findings state that the teacher has an important role in teaching and learning activities of children with special needs in the classroom, especially its role of helping and teaching children with special needs during the learning process in the classroom and helping the communication of children with special needs with their friends. In addition to helping in teaching and learning activities in class, the class teacher is also the main support of ABK in the classroom to get the curriculum in accordance with what is needed by ABK. In addition, special assistant teachers for special needs are needed to be able to analyze the needs of special needs